Angiotensin Receptor Neprilysin Inhibitor for Functional Mitral Regurgitation: PRIME Study. Issue 11 (12th March 2019) - Kang, Duk-Hyun; Park, Sung-Ji; Shin, Sung-Hee; Hong, Geu-Ru; Lee, Sahmin; Kim, Min-Seok; Yun, Sung-Cheol; Song, Jong-Min; Park, Seung-Woo; Kim, Jae-Joong
Abstract : Background: The morbidity and mortality of patients with functional mitral regurgitation (MR) remain high, but no pharmacological therapy has been proven effective. The hypothesis of this study was that sacubitril/valsartan would be superior to valsartan alone in improving functional MR via dual inhibition of the renin-angiotensin system and neprilysin. Methods: In this double-blind trial, we randomly assigned 118 patients with heart failure with chronic functional MR secondary to left ventricular (LV) dysfunction to receive either sacubitril/valsartan or valsartan, in addition to standard medical therapy for heart failure. The primary end point was the change in effective regurgitant orifice area of functional MR from baseline to the 12-month follow-up. Secondary end points included changes in regurgitant volume, LV end-systolic volume, LV end-diastolic volume, and incomplete mitral leaflet closure area. Results: The decrease in effective regurgitant orifice area was significantly greater in the sacubitril/valsartan group than in the valsartan group (–0.058±0.095 versus –0.018±0.105 cm 2 ; P =0.032) in an intention-to-treat analysis including 117 (99%) patients. Regurgitant volume was also significantly decreased in the sacubitril/valsartan group in comparison with the valsartan group (mean difference, –7.3 mL; 95% CI, –12.6 to –1.9; P =0.009). There were no significant between-group differences regarding the changes in incomplete mitral leaflet closure area and LV volumes, with the exception of LV end-diastolic volume index ( P =0.044). We noted no significant difference in the change of blood pressure between the treatment groups, and 7 patients (12%) in the sacubitril/valsartan group and 9 (16%) in the valsartan group had ≥1 serious adverse events ( P =0.54). Conclusions: Among patients with secondary functional MR, sacubitril/valsartan reduced MR to a greater extent than did valsartan. Our findings suggest that an angiotensin receptor-neprilysin inhibitor might be considered for optimal medical therapy of patients with heart failure and functional MR. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02687932. Abstract : Supplemental Digital Content is available in the text.